Femtosecond laser produced hydrophobic hierarchical structures on additive manufacturing parts - Jiao, Lishi (2018)
With the recent expansion of additive manufacturing (AM) in industries, there is an intense need to improve the surface quality of AM parts. A functional surface with extreme wettability would explore the application of AM in medical implants and microfluid. In this research, we propose to superimpose the femtosecond (fs) laser induced period surface structures (LIPSS) in the nanoscale onto AM part surfaces with the micro structures that are fabricated in the AM process. A hierarchical structure that has a similar morphology to a lotus leaf surface is obtained by combining the advantages of liquid assisting fs laser processing and AM. A water contact angle (WCA) of 150° is suggested so that a super hydrophobic surface is achieved. The scanning electron microscopy (SEM) images and X-ray photoelectron spectroscopy (XPS) analysis indicate that both hierarchical structures and higher carbon content in the laser processed area are responsible for the super hydrophobicity.